Tackling Workforce Constraints : For Equitable Care Amidst Rapid Growth and Urbanization - World Bank Group (World Bank, Washington, DC, 2019)
By 2050, sixty-eight percent of the world's population is expected to live in urban areas. As countries grow and urbanize, their disease burden shifts toward noncommunicable diseases (NCDs). Health workers must consequently expand the services they offer to include NCD prevention and control, while also providing access to high-quality services for infectious diseases. The growth of the private sector can exacerbate, rather than ameliorate, workforce shortages since its comparatively higher wages often motivate workers to leave the public sector. At the same time, the private sector can help fill gaps in specialist positions such as pharmacists and laboratory workers.